2019
DOI: 10.1177/0958305x19839276
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of parabolic trough solar collector with solar tracking tilt sensor for water distillation

Abstract: The distilled water production by the application of the parabolic trough solar collector technology has its significant importance that still needs further exploration. The current study represents the modification of parabolic trough solar collector, with the using of solar tracking tilt sensor with the continuous water circulation rate of 0.22 kg/s to enhance the productivity of the parabolic trough solar collector, and the tracking system consisting of low-speed 12 V motor units of 0.75 r/min and torque of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…m-2.day-1 with the solar chimney power generation-sea water desalination of the synthetic system. However, the results are not similar to the result [18], who observed that the average yield of distilled water was 2300 ml. m-2.day-1 in winter on the single solar wick type distillation plant.…”
Section: Figurecontrasting
confidence: 95%
See 4 more Smart Citations
“…m-2.day-1 with the solar chimney power generation-sea water desalination of the synthetic system. However, the results are not similar to the result [18], who observed that the average yield of distilled water was 2300 ml. m-2.day-1 in winter on the single solar wick type distillation plant.…”
Section: Figurecontrasting
confidence: 95%
“…Solar distillation plants can work by the natural water cycle, and it can receive the solar energy to warm the water so that the water boils and evaporates. The vapors are then condensed in distilled water forms as it cools down reported by [18]. The solar collector can be utilized for different purposes such as purification and distillation, dried water heating, heating of water for different purposes, lighting at night, and water pumping [19].…”
Section: Solar Collectorsmentioning
confidence: 99%
See 3 more Smart Citations